PENGARUH PENERAPAN INKLUSI KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Firdha Aksari Anindyntha (Program Studi Ekonomi Pembangunan, 2020)
The creation of financial system stability through the application of financial inclusion is a national development strategy to encourage economic growth. Financial inclusion consists of three indices, namely availability, access, and usage. The purpose of this research is to determine the effect of the application of financial inclusion on economic growth in Indonesia. The method in this study uses Partial Least Square (PLS) analysis because the independent variable (financial inclusion index) is a latent variable that has many indicators. The results of the analysis show that of the three financial inclusion indices, there are two indices that influence economic growth, namely availability with indicators of ATM machine availability and access with indicators of account ownership, debit cards, and e-money cards.